Reconstitution of pluripotency from mouse fibroblast through Sall4 overexpression - Lizhan Xiao; Zifen Huang; Zixuan Wu; Yongzheng Yang; Zhen Zhang; Manish Kumar; Haokaifeng Wu; Huiping Mao; Lihui Lin; Runxia Lin; Jingxian Long; Lihua Zeng; et al. (Nature Communications)
Abstract Somatic cells can be reprogrammed into pluripotent stem cells (iPSCs) by overexpressing defined transcription factors. Specifically, overexpression of OCT4 alone has been demonstrated to reprogram mouse fibroblasts into iPSCs. However, it remains unclear whether any other single factor can induce iPSCs formation. Here, we report that SALL4 alone, under an optimized reprogramming medium iCD4, is capable of reprogramming mouse fibroblasts into iPSCs. Mechanistically, SALL4 facilitates reprogramming by inhibiting somatic genes and activating pluripotent genes, such as Esrrb and Tfap2c. Furthermore, we demonstrate that co-overexpressing SALL4 and OCT4 synergistically enhances reprogramming efficiency. Specifically, the activation of Rsk1/Esrrb/Tfap2c by SALL4, alongside OCT4’s activation of Sox2 and the suppression of Mndal by SALL4 and Sbsn by OCT4, cooperate to facilitate SALL4+OCT4-mediated reprogramming. Overall, our study not only establishes an efficient method for iPSCs induction using the SALL4 single factor but also provides insights into the synergistic effects of SALL4 and OCT4 in reprogramming.